Determining the Degree of Agreement between Computed Tomography Scan and Saline Test to Detect Knee Space Invading in Penetrating Trauma - Fatemeh Mohammadi; Reza Mosaddegh; Samira Vaziri; Elham Zahedi (مجله دانشکده پزشکی اصفهان, 2018)
Background: Penetrating traumas to joints if not detected and properly treated, will be damaged, and causes intra-articular contamination and septic arthritis. At present, saline test is used to detect penetrating wound into the joint. Considering that it is invasive and painful, and is prone to infectious complications especially in busy emergency wards, the purpose of this study was to determine the consensus of computed tomography (CT) scan with saline test to increase the detection rate of penetrating knee trauma cases.